NFE2 and PF4 as biomarkers for BET inhibition-induced thrombocytopenia in preclinical and clinical studies - Zhang, Cindy; Xu, Ke; Wang, Faye; Price, Jennifer; Panzica, Julie; Coker, Shodeinde; Esposito, Oriana; Greenawalt, Danielle; Westhouse, Richard; Augustine-Rauch, Karen (Frontiers in Medicine, 2025)
IntroductionBromodomain and Extraterminal (BET) proteins play a crucial role in cellular proliferation and differentiation through the epigenetic regulation of gene transcription. As a result, inhibiting BET family proteins emerges as a promising epigenetic approach for treating various cancers. However, clinical trials have indicated that thrombocytopenia is a dose-limiting toxicity associated with BET inhibition. This study aims to explore the mechanism and clinical pharmacology of BMS-986158-induced thrombocytopenia and to identify biomarkers as tools to identify patients at higher risk, thereby better managing toxicity and improving efficacy.MethodsBlood samples from preclinical rats and clinical trial patients treated with BMS-986158 were collected for transcriptional expression profiling. Target engagement was confirmed by measuring HEXIM1 and monitoring thrombocytopenia following BET inhibition. Genes regulated by GATA1 and associated with thrombopoiesis, including NFE2 and PF4, were investigated. The outcomes of the rat and human studies were compared to identify biomarkers for the early prediction of thrombocytopenia associated with BET inhibition.ResultsTarget engagement was confirmed with dose-dependent responses of HEXIM1 expression and platelet counts. Blood samples from rats treated with BMS-986158 showed dose-dependent downregulation of GATA1, NFE2, and PF4 at 24 h or earlier post-treatment. Similarly, patients’ blood samples collected within 24 h post-treatment with BMS-986158 also showed dose-dependent downregulation of GATA1 and PF4 in all treated groups. Significant downregulation of PF4 and NFE2 genes was found in patients with low platelet counts. A strong correlation between the expression of GATA1 and the genes NFE2 and PF4 was observed in both preclinical and clinical studies.DiscussionThe consistent downregulation of GATA1, NFE2, and PF4 transcription within hours post-BMS-986158 treatment in both preclinical and clinical studies demonstrates that BET inhibitors induce thrombocytopenia by altering GATA1 gene expression and its downstream genes, NFE2 and PF4, which regulate megakaryopoiesis and thrombopoiesis. Early detection of transcriptional changes in blood samples during treatment courses positions NFE2 and PF4 as promising biomarkers for proactively monitoring and mitigating treatment-emergent thrombocytopenia.